Primary Liver Tumors in Turkey - Sebati ÖZDEMİR and Teoman SOSYAL and Hakan ŞENTÜRK and Muzaffer BEZGAL and Abdullah SONSUZ and Süha GÖKSEL and Perihan AKIN and Muzaffer GÜRAKAR (Turkish Journal of Gastroenterology, 2020)
-